2018
DOI: 10.1016/j.ribaf.2017.07.093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ex ante and ex post conservatism on the cost of equity capital: A quantile regression approach for MENA countries

Abstract: This paper aims to provide a deeper understanding of the relationship between accounting conservatism and the cost of equity capital (COEC). For this purpose, we use the quantile regression (QR) framework and examine the effect of two dimensions of conservatism (ex ante and ex post) on the COEC. This methodological contribution allows us to test whether the effect of the two forms of conservatism vary across the full distribution, especially at the extreme quantiles of the COEC. Empirical results from the QR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
3
9
0
1
Order By: Relevance
“…Thus, hypothesis which states that accounting conservatism lowers the cost of equity capital is proven and confirmed by empirical data. Li (2015), and Khalifa et al (2018) reporting that accounting conservatism lowers the cost of equity capital. The above results also reinforce the findings of Goh et al (2017) which prove that there is a decrease in equity capital costs when conservatism levels increase, Razzaq & Rui (2018) find that conditional conservatism lowers the cost of equity capital in Chinese companies, and Razzaq (2019) reports that conditional conservatism lowers the cost of equity capital in companies in Pakistan.…”
Section: ü Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hypothesis which states that accounting conservatism lowers the cost of equity capital is proven and confirmed by empirical data. Li (2015), and Khalifa et al (2018) reporting that accounting conservatism lowers the cost of equity capital. The above results also reinforce the findings of Goh et al (2017) which prove that there is a decrease in equity capital costs when conservatism levels increase, Razzaq & Rui (2018) find that conditional conservatism lowers the cost of equity capital in Chinese companies, and Razzaq (2019) reports that conditional conservatism lowers the cost of equity capital in companies in Pakistan.…”
Section: ü Analysis and Discussionmentioning
confidence: 99%
“…The main problem in agency relations is the emergence of information asymmetry, both in the context of adverse selection and moral hazard (Scott, 2015). The application of the conservatism principle is expected to lower the cost of the company's capital by reducing the number of dividends paid so that in turn lowers the agency conflict (Razzaq & Rui, 2018 Khalifa et al (2018). They proved that low quality of return has an impact on the high cost of equity capital.…”
Section: ü Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…The QR approach has been widely employed in different research fields like economic, finance, accounting and corporate governance and other fields outside management sciences. For example, in education economics, we find Arias et al (2001), Buchinsky (1994, 2001), Eide and Mark (1998), Chernozhukov and Umantsev (2001) and Bassett and Chen (2001) in mutual fund investment styles, Engel and Manganelli (2004) in value at risk, Meligkotsidou et al (2009) in hedge fund strategies, Li and Miu (2010) in bankruptcy prediction, Barreto and Hughes (2004) in economic growth studies, Li and Hwang (2011) and Khalifa et al (2018) in accounting, Ramdani and Witteloostuijn (2010) in corporate governance, Buchinsky (1994), Garcia et al (2001), Machado and Mata (2001) and Nielsen and Rosholm (2001) in wage analysis.…”
Section: Quantile Regressionmentioning
confidence: 92%
“…In order to estimate equations ( 1) and ( 2), the literature showed that the standard OLS method provides a partial view of the relationship between variables by focusing on the conditional mean of the dependent variable (Koenker and Hallock, 2001). Furthermore, this technique may suffer from the presence of outliers or extreme values that may cause the non-normality of the dependent variables, and therefore violate the normality assumption of residuals in the OLS regression (Khalifa et al, 2017). Following the study by Koenker and Bassett (1978), the quantile regression approach is considered to deal with the technical issues related to the OLS regression method.…”
Section: Econometric Analysismentioning
confidence: 99%